Epidemiology of eye injuries sustained by military personnel in China - XIAO Jian-he; ZHANG Mao-nian; JIANG Cai-hui; ZHANG Ying; QIU Huai-yu (Chinese Journal of Traumatology, 2012)
【Abstract】Objective: To investigate the epidemiological characteristics of eye injuries sustained by military personnel in Chinese army. Methods: Eleven military evacuation hospitals located in different regions were selected for this study. We reviewed all the medical records of eye injuries sustained by military personnel between January 2005 and December 2009. Patients?information was collected. All data were put into database and analyzed statistically. Results: Totally there were 415 inpatients with eye injuries (442 eyes) and their mean age was 24.40 years. Eye injury accounts for 13.51% of all eye diseases in this study. From 2006 to 2009, the number of eye injury increased gradually. Among them, 175 (42.17%) were injured in leisure time, and 145 (34.94%) in working time. Twenty-two (5.30%) patients had an eye surgery or history of eye disease before injury. In all, 246 patients (59.28%) were sent to evacuation hospital within 24 hours and 64 (56.64%) underwent surgeries in 24 hours after injury. There were 389 patients (93.73%) hospitalized for 1 time. Visual acuities of 187 eyes (42.31%) were grade 1 (≥20/40) after injury. When discharge, 349 eyes (78.96%) obtained a visual acuity of grade 1. Conclusion: Eye injury has a very frequent incidence in Chinese army and much more attention should be paid to prevent it. Key words: Epidemiology; Eye injuries; Military hygiene; Military personnel